2020
DOI: 10.1007/s00125-020-05127-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations of birthweight and history of childhood obesity with beta cell mass in Japanese adults

Abstract: Aims/hypothesis Low birthweight is associated with a high risk of diabetes, but there are no reports discussing birthweight and pancreatic tissues in humans. The purpose of this study was to examine the correlation between birthweight and beta and alpha cell mass in humans. Methods Sixty-four Japanese adults with and without diabetes who underwent pancreatectomy and were able to recall their weight history including birthweight were included. Pancreatic tissues were stained for insulin and glucagon, and fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 48 publications
(72 reference statements)
0
21
1
1
Order By: Relevance
“…The characteristics of the participants have been reported previously [ 10 ] and are shown in ESM Table 1 . The Ethics Committee of Keio University School of Medicine approved this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of the participants have been reported previously [ 10 ] and are shown in ESM Table 1 . The Ethics Committee of Keio University School of Medicine approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…Preoperative HbA 1c was measured by HPLC (HLC723G11; Tosoh, Tokyo, Japan). Participants were asked about their detailed weight trajectory using a questionnaire, as previously reported [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since beta-cell replication is more frequently observed in the first five years of life [ 29 , 30 ], childhood obesity or birthweight might affect beta-cell mass. Indeed, we recently reported that the beta-cell area and birthweight were positively correlated in adults with NDM, and the beta-cell area in the group with a history of childhood obesity was increased compared with that in subjects without a history of obesity [ 26 ].…”
Section: Beta Cell Mass In Obesity and Type 2 Diabetesmentioning
confidence: 99%